2006
DOI: 10.1038/sj.npp.1301249
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Receptor β, but not α, Mediates Estrogen's Effect on Cocaine-Induced Reinstatement of Extinguished Cocaine-Seeking Behavior in Ovariectomized Female Rats

Abstract: Preclinical and clinical studies indicate that females are more vulnerable to relapse than males, and the neurobiological effects of estrogen are thought to mediate, in part, the sex differences in cocaine-taking behavior. The goal of the present study was to investigate the involvement of estrogen receptor a (ERa) and b (ERb) in estrogen-mediated increases in cocaine-induced reinstatement of extinguished cocaine-seeking behavior in ovariectomized (OVX) female rats. Rats were initially trained to self-administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 78 publications
(111 reference statements)
5
47
1
Order By: Relevance
“…The results of the present study were not consistent with the tentatively hypothesized negative relationship between estradiol level and abstinence, which was based primarily on preclinical research suggesting estradiol may have a facilitative effect on cocaine related sensitization, self-administration and relapse/reinstatement. [51][52][53][54][55][56][57] Since there is no preclinical research examining the effects of estradiol in nicotinereinforced behavior (e.g., self-administration), the lack of association between estradiol and abstinence observed here is consistent with the possibility that estradiol may not have uniform effects across different substances of abuse.…”
Section: Discussionsupporting
confidence: 69%
“…The results of the present study were not consistent with the tentatively hypothesized negative relationship between estradiol level and abstinence, which was based primarily on preclinical research suggesting estradiol may have a facilitative effect on cocaine related sensitization, self-administration and relapse/reinstatement. [51][52][53][54][55][56][57] Since there is no preclinical research examining the effects of estradiol in nicotinereinforced behavior (e.g., self-administration), the lack of association between estradiol and abstinence observed here is consistent with the possibility that estradiol may not have uniform effects across different substances of abuse.…”
Section: Discussionsupporting
confidence: 69%
“…In a similar experiment, Carroll and colleagues found that acute or chronic estradiol enhanced reinstatement of responding for cocaine [73]. In another experiment, an agonist for estrogen receptor-ß (ERß), but not an agonist for estrogen receptor-α (ERα), was effective at reinstatement of responding when primed with 5 mg/kg cocaine [72]. Only one dose of the agonists were used, so it is possible that higher doses of the ERα agonist might have also been effective.…”
Section: Sex Differences In Stimulant Self-administration In Animalsmentioning
confidence: 85%
“…Only one dose of the agonists were used, so it is possible that higher doses of the ERα agonist might have also been effective. Interestingly, at higher doses of cocaine, responding was re-initiated whether or not the animals were treated the ERß agonist [72]. Thus, estradiol rapidly enhances the subjective effects of cocaine to reinstate responding for access to cocaine, but estradiol does not reinstate responding on its own.…”
Section: Sex Differences In Stimulant Self-administration In Animalsmentioning
confidence: 87%
“…Body weights were recorded daily. OVX was performed according to a previous study (Larson & Carroll, 2007), and the experimental protocols followed the guidelines of the Guide for the Care and Use of Laboratory Animals and were approved by the Laboratory Animal Care and Use Committee of the Beijing Institute of Radiation Medicine.…”
Section: Animalsmentioning
confidence: 99%